Does mouthwash degrade the force of orthodontic latex elastics? - Ananto Ali Alhasyimi; Sri Suparwitri; Niswati Fathmah Rosyida (Intelektual Pustaka Media Utama, 2022)
With the surge of COVID-19 pandemic, orthodontists have recommended the use of mouthwashes. However, this product often includes substances that change the pH of the oral environment and potentially alter orthodontic elastic force. This study aimed to investigate the effect of several mouthwashes on the force decay of latex elastics. A total of 100 orthodontic latex elastics (1/4”) were separated into five groups: control, zinc sulfate 0.2%, chlorhexidine 0.2%, sodium fluoride 0.2%, and povidone–iodine 1%. The samples were all stretched to 19.05 mm, stored in artificial saliva solutions, and housed in an incubator. Every 12 hours, the specimens from groups 2–5 were immersed in the test mouthwashes for 60 seconds and immediately returned to the artificial saliva. A tension gauge with five times that of the activation was used to measure force. Elastic force was tested at five-time intervals: baseline, 1, 6, 12 and 24 hours. Statistical analysis was conducted using two-way ANOVA and Tukey post hoc test. Results showed statistical differences for the time intervals and force degradation of orthodontic latex elastics (P<0.05). The majority of force loss occurred within 6 hours of extension and immersion. Mouthwashes had no influence on the reduction in elastic force (P>0.05). The force degradation of orthodontic latex elastics was unaffected by mouthwashes. The lowest force degradation was generated by povidone–iodine, followed by zinc sulfate, sodium fluoride, and chlorhexidine.